Henri Le Saux et le psychisme - Fabrice Blée (Recherches Germaniques)
Henri Le Saux is one of the great Christian mystics of the twentieth century and a pioneer of dialogue with Hinduism. For the French Benedictine, co-founder of the first Catholic ashram, the grace of India lies in its message of interiority, which is Within. No awakening to God without awakening to oneself. We propose to grasp the way in which he understands the psyche, as well as the contribution of India from which it has benefited. To this end, we adopt a three-phase development that provides information on the origin of his understanding of the psyche, its development and the articulation of its main constituing elements that constitute it. First, this understanding is based on the monk’s relationship to the ‘living God’ in reference to the experience of non-duality (advaita); second, it unfolds in a process of self-knowledge and through the challenge of a certain self-understanding; third, it is articulated according to a Trinitarian approach of the soul between consciousness and unconsciousness. We conclude with some features of India’s image that emerges from this approach of the human psyche.